Integration and economic viability of fueling the future with green hydrogen: An integration of its determinants from renewable economics. (8th November 2021) - Xiang, Huang; Ch, Paramaiah; Nawaz, Muhammad Atif; Chupradit, Supat; Fatima, Arooj; Sadiq, Muhammad
Abstract: The volatility of fossil fuel and their increased consumption have exacerbated the socio-economic dilemma along with electricity expenses in third world countries around the world, Pakistan in particular. In this research, we study the output of renewable hydrogen from natural sources like wind, solar, biomass, and geothermal power. It also provides rules and procedures in an attempt to determine the current situation of Pakistan regarding the workability of upcoming renewable energy plans. To achieve this, four main criteria were assessed and they are economic, commercial, environmental, and social adoption. The method used in this research is the Fuzzy Analytical Hierarchical Process (FAHP), where we used first-order engineering equations, and Levelized cost electricity to produce renewable hydrogen. The value of renewable hydrogen is also evaluated. The results of the study indicate that wind is the best option in Pakistan for manufacturing renewable based on four criteria. Biomass is found to be the most viable raw material for the establishment of the hydrogen supply network in Pakistan, which can generate 6.6 million tons of hydrogen per year, next is photovoltaic solar energy, which has the capability of generating 2.8 million tons. Another significant finding is that solar energy is the second-best candidate for hydrogen production taking into consideration its low-cost installation and production. The study shows that the cost of using hydrogen in Pakistan ranges from $5.30/kg to $5.80/kg, making it a competitive fuel for electric machines. Such projects for producing renewable power must be highlighted and carried out in Pakistan and this will lead to more energy security for Pakistan, less use of fossil fuels, and effective reduction of greenhouse gas emissions. Highlights: Green hydrogen energy is a clean alternative fuel to increase energy security. Sustainable Solution for Severe Energy Crises in Emerging Economies. Comparisons of various renewable energy sources to produce hydrogen. The guarantee of hydrogen origin is essential to ensure its energy cleanness.